Case Study Literature Review (Sclr) Effectiveness Of Lavender Aromatherapy And Thought-Stopping Therapy To Reduce Anxiety In Primary Post-Partum Mothers At Tarogong Public Health Center, Garut City In 2025 - Mulia Fujianty; Hidayani Hidayani; Lina Nurul Izza (Universitas Dharmawangsa Medan, 2026)
The postpartum period is the beginning of a new family for young families, so it is necessary to adapt to their new roles, because family responsibilities increase with the birth of their baby. A holistic approach involving education, psychological support, and monitoring of maternal mental health during the postpartum period is needed to reduce the risk of psychological disorders and ensure the well-being of both mother and baby. The purpose of this study was to compare the effectiveness of lavender aromatherapy and thought stopping therapy as an effort to reduce anxiety in primiparous postpartum mothers. This type of research is a Pre-Experimental Design using One Group Pre-test and Post-Test Design. In this study, there were 2 samples where 1 sample used lavender aromatherapy intervention and 1 sample thought stopping therapy intervention. The study was conducted at PKM Tarogong and was conducted in August 2025. The study used univariate analysis to describe midwifery care and to determine the effectiveness of lavender aromatherapy with thought stopping therapy on reducing anxiety levels of primiparous postpartum mothers at PKM Tarogong in 2025. The results showed that both interventions were equally effective in reducing anxiety levels of primiparous postpartum mothers. Thought-stopping therapy reduced anxiety scores by 13 points within 3 days, while lavender aromatherapy reduced anxiety scores by 12 points within 7 days. Thus, thought-stopping therapy was deemed quantitatively more effective and faster in reducing anxiety, while lavender aromatherapy remains relevant as a safe and easy-to-implement complementary therapy. Suggestions for primiparous postpartum mothers are expected to increase their knowledge about non-pharmacological anxiety reduction methods such as lavender aromatherapy and thought-stopping therapy